Potential for sharing of common regional resources in the Eastern Himalayan Region : focus on Sapta Kosi High Dam Project - Ahmad, Qazi Kholiquzzaman, 1943-; Bangladesh. Paribeśa o Bana Mantraṇālaẏa.; United Nations Development Programme (Bangladesh); Sapta Kosi High Dam Project (Dhaka : Bangladesh Unnayan Parishad, 2004)
With reference to the Project area in India, Bangladesh, and Nepal.
"With support from Ministry of Environment and Forest, Government of Bangladesh under the technical assistance of United Nations Development Programme"--added t.p.
Includes bibliographical references (p. [145]-148) and index.
Keywords: Water-supply -- Himalaya Mountains Region; Water resources development -- Himalaya Mountains Region; Global commons -- Himalaya Mountains Region; Sapta Kosi High Dam Project